Implementación de un sistema de control de gestión con las metodologías del balanced scorecard y gestión por procesos en una pymes comercial en la ciudad de Guayaquil durante el año 2007 - Gonzalez, Virginia (2009)
This work will allow us to know the Methodology based on the Balanced Scorecard and the important thing that it is its implantation in the companies generally, becoming a powerful and useful tool that allows the continuous understanding between the formulation and implantation of the strategy and the accomplishment of the management control and interrelating the traditional indicators of control with financial indicators and no financiers to altogether measure the profits of the strategic targets from the point of view of the clients, the shareholders, the internal processes and learning. The fundamental advantage of the methodology is that it is not only confined to a perspective, but considers all simultaneously, identifying the relations among them. Of this form it is possible to establish a chain cause - effect that allows taking the necessary initiatives in each level. Knowing how the objectives of the different perspective connect, the results of the indicators that have been obtained progressively allow to see if there is to make adjustments in the chain, initiatives or handles of value, to assure that the goals are fulfilled. This way the human, technological resource, information and cultural are fortified, demanded by the processes, and these are aligned with the expectations of the clients.